Productivity enhancement at home via cross‐border acquisitions: The roles of learning and contemporaneous domestic investments - Bertrand, Olivier; Capron, Laurence (Strategic Management Journal, 2015)
We examine whether ex post domestic productivity gains accrue to firms making cross‐border acquisitions. We argue that cross‐border acquisitions can enhance the acquirers' productivity at home, and we posit that these domestic productivity gains will be greater when there are learning opportunities in the target's host country and when contemporaneous domestic productivity‐enhancing investments are made by the acquirer in conjunction with the acquisition. These predictions are supported by data drawn from a sample of French acquiring and nonacquiring firms. Our results indicate that cross‐border acquisitions and investing in productivity at home are complementary: each makes the other more beneficial to firm productivity . Copyright © 2014 John Wiley & Sons, Ltd.